Anti-herpetic activity evaluation of Salvia uliginosa exudate and Icetexone diterpene - Maria,; Grismino, Alexia; Alves, Diogo; von Poser, Gilsane; Roosevelt Torres Romão, Pedro; Rodrigues Junior, Luiz Carlos (International Journal of Phytomedicine, 2025)
Herpes Simplex Virus-2 (HSV-2) is a dermotropic virus. Recent studies indicate that the percentage of HSV-2 infections in Brazil is 11.3%, and it is estimated that approximately 90% of the world's population has a positive serology for one or both viruses. HSV-2 is a sexually transmitted infection that leads to serious problems in individuals with weakened immune systems or those undergoing immunosuppressive treatment. Furthermore, primo-infections or recurrent infections present a high risk of transmission from mother to child during delivery. Existing antiviral treatments are not effective during the latency phase, and some strains are already resistant to the primarily used drug acyclovir. Therapies using plant derivatives have proven effective in the treatment of herpes. Some species of Salvia have already been studied and have demonstrated efficacy against viruses and other microorganisms. Analyses published by our group have demonstrated that Salvia uliginosa exhibits significant activity against Leishmania amazonensis, an intracellular parasite responsible for causing leishmaniasis. Our objective was to evaluate and characterize the possible antiherpetic effects of S. uliginosa against HSV-2 in vitro. S. uliginosa was collected and identified by a botanist. The plant exudate and major compound, the diterpene Icetexone (ICT), were obtained from the Pharmacognosy Laboratory of the Federal University of Rio Grande do Sul. ICT was isolated in the same laboratory via column chromatography using silica gel. The MTT assay was used on the VERO cell line to analyze the cytotoxicity of the extracts and isolated compounds, determining the IC50 and CC50 values. A plaque assay was used to evaluate the virucidal effect of the plant exudate and ICT on HSV-2. These results indicated that the exudate of S. uliginosa has anti-herpetic activity, although ICT does not. Further experiments are required to elucidate the mechanism of action.